The Factors Influencing Second-Hand Clothing Purchase Decision on Facebook Page in Thailand - Pankham, Sumaman; Kanchanarotphan, Nawiya (Journal of Multidisciplinary in Humanities and Social Sciences, 2022)
This article aimed to develop and validate the consistency of a causal relationship model of second-hand clothing purchase decisions and to study causal factors affecting second-hand clothing purchase decisions on the Facebook Page in Thailand. The study was quantitative research. The sample was people who have clothing purchase decisions on the Facebook page of consumers in Thailand of 414 people. The tools used in the research were online questionnaires. The statistics used in the data analysis were frequency, percentage, and structural equation models. The results of this research were the development of causal relationship models consisting of 4 components. They are: 1) perceived value, 2) service quality, 3) purchase intention and 4) purchase decision and the model is consistent with the empirical data to a great extent. The statistics showed the Chi-square statistics goodness fit test (χ2) = 166.23, degrees of freedom (df) = 135, CMIN/df = 1.23, GFI = 0.96, AGFI = 0.94, SRMR = 0.03, RMSEA = 0.02. The result was a predictive coefficient of 0.85, indicating that the variables in the model can explain the variance of the clothing purchase decisions on the Facebook page by 85 percent. It was found that purchase intention, perceived value, and service quality were respectively influenced by purchase decisions. The results of this research are useful for entrepreneurs. The second-hand clothing businesses are utilized to market plan and create marketing strategies that are suitable for consumer behavior. The result of this research could apply to the purchasing intention of clothing purchase decisions in the future.